Trattamento delle fratture periprotesiche dell’anca: sintesi vs revisione - Colombi, A.; Castelli, C.C. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC HIP FRACTURE: ORIF VS REVISION SURGERY Femoral periprosthetic fractures in hip surgery still represent a difficult surgical procedure and a secure optimal treatment has not been found yet. Great help is provided by the development of commonly used classifications such as the Vancouver classification and the recent Unified Classification System (UCS), which introduce clearer fracture patterns with the respective surgical indications. The most discussed pattern is related to category B of both classifications in which, despite the use of established treatment paradigms, results are poor or otherwise unpredictable. This study reviews the literature related to the analysis of fractures and its following treatment.